Effect of Irradiation and Curry Leaves Extract on Quality Attributes and Shelf Life of Chicken Emulsion - Muthukumar, M.; Ravi, T.; Kumar, M. Shashi; Reddy, K. Sudhakar; Krishnaiah, N. (Journal of Meat Science, 2014)
The present study was conducted to evaluate the effect of irradiation and antioxidants on quality attributes and shelf life of the chicken emulsion during refrigerated storage. Four treatments evaluated include: Control (without irradiation and antioxidant), T1 (irradiation without antioxidant), T2 (butylated hydroxyl anisole–(BHA) - 0.02%) and T3 (450 ppm equivalent curry leaves (Murrayakoenigii) phenolics. Total phenolic contents (mg per gram of powder) as tannic acid equivalent of curry leaves was ranged from 6.78 to 7.27. There was a concentration dependent increase in reducing power (absorbance value of 0.3 at 50 μg phenols to 0.9 at 50 μg phenols) and 1,1-diphenyl 2-picrylhydrazyl (DPPH) radical scavenging activity (70% at 50 μg phenols to 85% at 250 μg phenols) of curry leaves extract. Highly significant differences (P<0.05) in pH, TBARS (Thiobarbituric acid reactive substance) values and microbial counts was observed between control and treatment groups and also between storage periods. Incorporation of curry leaves extract significantly (P<0.05) lowered TBARS values. During storage, all the samples showed significant (P<0.05) decrease in pH and an increase in TBARS values and total plate counts, psychrotropic counts and lactobacilli counts. Escherichia coli and Salmonella were not detected in all the treatment groups. No significant (P>0.05) difference was noticed in sensory attributes among the control and treatment groups up to 7 days of storage. However, the deteriorative changes were faster in control samples. Thus, the present study indicated the promising potential of irradiation as an efficient method for reducing microbial load in meat products and curry leaves extract may be used as a potential source of antioxidants to protect against oxidative rancidity.